MODAL SOSIAL DAN KEBERLANGSUNGAN USAHA PEDAGANG SAYURAN DI PASAR BERSEHATI MANADO - _, Nurhadiyono; Purwanto, Antonius; Tumengkol, Selvie M. (Universitas Sam Ratulangi, 2019)
As a community economic institution, the market is an expression of social relations. This is due to economic activity being an integral part of social life. The traditional market is still a trading center for basic materials and is the main goal in marketing the produce of agricultural, livestock, and fisheries. In this case the traditional market is functioning closer to the distance between consumers and producers to meet the needs of life. Bersehati Market is one of the largest markets in Manado city, where the traditional market operates 24 hours nonstop and daily activities without holidays. Vegetables are a fast-damaged commodity that requires special handling, that is to require vegetable traders to distribute to consumers faster so that the marketing path is as short as possible, knowing the nature of Vegetable traders need a network as a bond between each other. The availability of network in vegetable traders in the Bersehati market is a top priority to gain access to marketing, distribution and information on the availability of goods.Social networks that grow in a community of vegetable traders are very likely to contribute significantly in supporting the fluency activity in vegetable trading. Social networking plays an important role in distributing and marketing goods in the markets of Bersehati.This research is a study using a qualitatively descriptive approach. Where the research seeks to provide descriptive descriptions or descriptions, of a systematic and actual collection of objects examined in the facts.Good relations, avoiding forms of deviations against social norms that apply in trade so as to create a sense of social solidarity. The economic actions performed both are related to the sustainability of the capital, marketing tends to be colored with social relationships in relation to the network.Keywords: social capital, vegetable trader, marketing